PENGARUH MODAL AWAL, LAMA USAHA DAN JAM KERJA TERHADAP PENDAPATAN PEDAGANG KIOS DI PASAR BINTORO DEMAK - Rosetyadi Artistyan Firdausa; Fitrie Arianti (Diponegoro Journal of Economics, 2013)
Trader income influenced by various factors. This study uses the following variables: initial capital, long of efforts, and working hours. This study aimed to investigate the influence of capital, long of effort and working hours to merchants income at market Bintoro Demak. Methods used to collect primary data was random sampling method. The study took 75 respondents as sample. The analysis uses multiple linear regression with income as the dependent variable and three independent variables are initial capital (Rp), long of effort (years) and working hours (h).Result of irregularities classical assumptions test showed the data were normally distributed and did not obtained a deviation. Based on calculations of SPSS 16.0, obtain F values of 61.009 with a significance of 0000. Using significance of 0.05 obtained of F table is 2.73, then F value (61.009)> F table (2.73), or the significance of F of 0.000 indicates less than 0.05 so it can be concluded that the three independent variables the initial capital, long of efforts as well as working hours jointly affect the amount of merchants revenue at market Bintoro Demak accepted. Partially, initial capital variables, long of effort and working hours affect significantly. From the three variables, the most dominant influence on the amount of traders income is capital variable, with t-value of 9.041 at probability of significance of 0.000.